Composition of Flavonoids in the Petals of Freesia and Prediction of Four Novel Transcription Factors Involving in Freesia Flavonoid Pathway - Zhu, Jiayi; Guo, Xueying; Li, Xin; Tang, Dongqin (Frontiers in Plant Science, 2021)
Freesia hybrida is rich in colors with beautiful flower shapes and pleasant aroma, and is of great ornamental value. Flavonoids are vital to its color formation. In this study, different developmental stages of the five Freesia cultivars were studied on level of their flavonoids accumulation and flavonoid-related genes expression. Based on the quantification of flower color phenotypes, UPLC-Q-TOF-MS was used to qualitatively and quantitatively quantify the flavonoids in them. Combined with transcriptome sequencing technology, the molecular mechanism of the metabolism difference in Freesia flavonoids was revealed, and the transcriptional regulatory mechanism of its flavonoid biosynthesis was further explored. A total of 10 anthoxanthin components were detected by UPLC-Q-TOF-MS. At the same time, a total of 12 anthocyanin components were detected, including cyanidin, delphinidin, petunidin, peonidin, malvidin and pelargonidin. In orange, yellow, and white cultivars, anthoxanthins gradually decreased with the opening of the petals; while in the red and purple cultivars, anthoxanthins firstly increased and then decreased as the flowers opened, and anthocyanins rised with the opening of the petals and reached their maximum in the Flowering Stage. The color of Freesia petals was closely related to the composition and content of anthoxanthins and anthocyanins. Petals of 5 cultivars were selected, using the Illumina Hiseq sequencing platform for transcriptome sequencing, and a total of 100,539 unigenes were obtained. There are totally 5,162 DEGs when the 4 colorful cultivars compared with the white cultivar in the stage 3. Comparing all DEGs with GO, KEGG and Pfam databases, it was found that flavonoid biosynthesis pathway genes were significantly different. Quantitative real-time PCR (qRT-PCR) technology was used to analyze the expression patterns of the structural genes of flavonoid biosynthesis pathway in Freesia petals and the transcription factors regulating this pathway were further explored. Our results showed that metabolic process was affected by structural genes in the flavonoid biosynthesis pathway such as CHS1, CHI2, DFR1, and FLS1. Four novel candidate transcription factors of WRKY and AP2 family may participate in its biosynthesis regulation, thus controlling its color forming in Freesia tepals.